2020
DOI: 10.1055/a-1110-7441
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Nerve Atrophy After Vestibular Neuritis – Results from a Prospective High-Resolution MRI Study

Abstract: Purpose Sudden unilateral peripheral vestibular deficit is mostly termed vestibular neuritis (VN), even if its cause or the exact location of the lesion remains unclear. Thus, therapy is mostly symptomatic. We aimed to prove if there is peripheral atrophy after VN with persistent canal paresis. Methods After approval by the ethics committee and according to the declaration of Helsinki and with informed consent, ten patients with persistent canal paresis after VN and ten age-matched healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…A study on vestibular nerve atrophy magnetic resonance imaging (MRI) in VN observed a statistically significant decrease in the cross-sectional area and height of the vestibular nerve, compared to the parameters of the contralateral vestibular nerves [ 15 ]. However, another investigation showed that only half of the participants had vestibular nerve atrophy and the others did not [ 16 ]. Therefore, it can be concluded that vestibulo-ocular reflex (VOR) examinations are still of great importance, e.g., using the caloric test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on vestibular nerve atrophy magnetic resonance imaging (MRI) in VN observed a statistically significant decrease in the cross-sectional area and height of the vestibular nerve, compared to the parameters of the contralateral vestibular nerves [ 15 ]. However, another investigation showed that only half of the participants had vestibular nerve atrophy and the others did not [ 16 ]. Therefore, it can be concluded that vestibulo-ocular reflex (VOR) examinations are still of great importance, e.g., using the caloric test.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous research reported that persistent canal paresis resulted in significant atrophy of the superior vestibular nerve observed by MRI. However, since half of the patients did not show significant differences compared to the control group, these results should be confirmed, including a larger sample size [ 16 ]. Another study stated that the CP results were pathological in 76% of the follow-up stage, indicating a persistent CP value in the VN.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies can also demonstrate contrast enhancement of the vestibular nerve, in particular the superior vestibular nerve, one to four hours after gadolinium injection [26,47,153]. Finally, one study showed that high-resolution MRI examinations ≥ 6 months after symptom onset in patients with a persistent peripheral vestibular deficit revealed atrophy of the vestibular nerve in 5 of the 10 patients examined, in particular of the superior vestibular nerve [53].…”
Section: Imagingmentioning
confidence: 99%
“…Patients with VN suffer from persistent vertigo and fear of exercise, leading to exacerbation of the disease and a vicious cycle that affects treatment outcomes [ 16 ]. This study, through cognitive, medication, and rehabilitation therapy, may improve patient motivation for rehabilitation and contribute to improved balance function and reduced severity of condition [ 17 ].…”
Section: Discussionmentioning
confidence: 99%